PENGARUH KEGIATAN SEKTOR EKONOMI TERHADAP KINERJA LALU LINTAS DI RUAS JALAN KELURAHAN VIM DISTRIK ABEPURA (Studi Kasus: Ruas Jalan Perkutut, Mako Brimob – Kantor Pos Kotaraja) - Muhammad Bayu Kholil Abdusalam; Monita Yessy Beatrick; Sudiro Sudiro (Fakultas Teknik Universitas Cenderawasih, 2022)
Economic activity becomes a benchmark in the assessment of the community to achieve prosperity, and becomes a supporter and driver of growth in the surrounding area. Vim Village, Abepura District is one of the service activity centers that has a land use that is so complex and strategically located that it triggers various forms of economic activity, becoming an attraction for people to travel for transportation, especially along Jalan Perkutut. This study examines the relationship of micro-economic activities with traffic performance obtained from side barriers, vehicle volume and road capacity. The research methods used to achieve the objectives are quantitative methods and qualitative methods. The quantitative method uses the analysis of the Indonesian Road Capacity Manual (MKJI, 1997) to obtain vehicle volume, road capacity and traffic performance. The qualitative method uses descriptive analysis that discusses the comparison of the distribution of micro-economic activities that affect side barriers, the comparison of two traffic performance results and spatial planning plans along the Perkutut road. The results showed that the increase in the number of micro-economic activities at night along Jalan Perkutut had an effect on increasing the number of side barriers and the volume of vehicles. In addition, the imbalance in the volume of vehicles and road capacity shows that Perkutut Road traffic performance is experiencing congestion as indicated by the Service Level Index (ITP) with a value of F. Under these conditions, spatial planning for the road network, pedestrian pedestrian arrangement and land use arrangement is needed, especially on microeconomic activities.